Analisa Sistem Pembumian Pada Pembangkit Listrik Tenaga Minihydro Di Tukad Balian Kabupaten Tabanan - I Made Darmayusa; I Gusti Ngurah Janardana; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2019)
Earthing systems (Grounding System) is a device that serves to secure the installation of overcurrent and overvoltage caused by lightning electricity or internal interruption of electricity by removing the payload to the ground. One of the factors that influence terhadapnilai prisoners earthing is resistivity value of the land. Mini-hydro power plants in Tukad Balian Tabanan regency require resistance value ? 2 Ohms. The purpose and benefits of the research was to determine the characteristics of the grounding system in the mini-hydro power plants in Tukad Balian Tabanan regency. And the benefits of this research is in order to get the data that can be used as a reference darii mounting / grounding system planning power plants Tukad Balian minihidor in Tabanan regency.Based on analysis of the calculation of the earthing system with some type used sebagau obtained the following results: by using a single type of rod electrodes (one rod) to obtain the results of the grounding prisoners ?2?, rod electrodes implanted deep as 13 meters. By using two types of rod electrodes (two rod) S> L to get the grounding ?2?, rod electrodes implanted with a length of 7 meters and the distance between the electrodes 9 meters. By using two types of rod electrodes (two rod) S <L to get the grounding ?2?, rod electrodes implanted with a length of 8 meters and the distance between the electrodes 2 meters. By using the type of plate to get the grounding ?2?, required as many as three pieces of plate with a depth of 1 meter. Using a type of grid to earthing ?2? result, a long electrode required 45 meter.